2019
DOI: 10.1101/866137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysical analysis ofPlasmodium falciparumHsp70-Hsp90 organizing protein (PfHop) reveals a monomer that is characterised by folded segments connected by flexible linkers

Abstract: Plasmodium falciparum causes the most lethal form of malaria. The cooperation of heat shock protein (Hsp) 70 and 90 is important for folding of a select number of cellular proteins that are crucial for cyto-protection and development of the parasites. Hsp70 and Hsp90 are brought into a functional complex that allows substrate exchange by stress inducible protein 1 (STI1), also known as Hsp70-Hsp90 organizing protein (Hop). P. falciparum Hop (PfHop) co-localises and occurs in complex with the parasite cytosolic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We previously resolved the structure of PfHop using SAXS analysis. Our previous study demonstrated that the TPR domains of PfHop assemble like "beads on a string'' (Makumire et al, 2020). This arrangement allows Hsp70 and Hsp90 to slide through the concave-shaped TPR domains to facilitate interaction.…”
Section: Figure 10mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously resolved the structure of PfHop using SAXS analysis. Our previous study demonstrated that the TPR domains of PfHop assemble like "beads on a string'' (Makumire et al, 2020). This arrangement allows Hsp70 and Hsp90 to slide through the concave-shaped TPR domains to facilitate interaction.…”
Section: Figure 10mentioning
confidence: 99%
“…An additional construct, pQE30-PfHsp70-1 NBD encoding for the NBD of PfHsp70-1 was similarly used to express the truncated version of this chaperone (Zininga et al, 2016). The production of recombinant protein was induced by isopropylthiogalactoside (IPTG) and the protein was purified using sepharose nickel affinity chromatography (Makumire et al, 2020(Makumire et al, , 2021. The expression and purification of recombinant proteins were analyzed by SDS-PAGE and confirmed by Western blot analysis using α-PfHsp70-1 (Shonhai et al, 2008), α-PfHop (Gitau et al, 2012), and α-His antibodies, respectively.…”
Section: In Silico Docking Of Pes Onto Pfhsp70-1 and Pfhopmentioning
confidence: 99%